Clubes negros de futebol em Santa Maria no pós-abolição (1916- 1932) - Lima, Taiane Anhanha (2023)
In this paper, through the investigation of two black soccer teams that existed in Santa MariaRS, the Club Foot Ball 7 de Setembro and Sport Club Rio Branco, the first founded in 1916 and the second being mentioned in the sources in 1920, we seek to understand the post-Abolition context from the point of view of black soccer clubs. Thinking of this sport as a means of social integration, black sociability, but also of protest against racism, we found several references of these black clubs created in cities of Rio Grande do Sul. In the same way, we noticed how common relationships and trips to inter-city games between these teams were. Important research on the post-abolition period and slavery in Santa Maria has been produced in recent years, studies on the trajectories of social and collective subjects, with emphasis on black organizations, which make it possible to understand the various forms of black resistance in the period, but black soccer associations are only found in brief citations or were not the focus of the authors' analysis. Facing the national context of racial segregation in some elite soccer clubs or leagues in the early twentieth century, we tried to understand whether the city fit into this situation or not. Investigating the phenomenon of the creation of these black soccer clubs, besides better understanding the post-Abolition and the ethno-racial relations in the city and in the state, proves relevant because we are listening to the voices of the past, which for a long time were hidden by a traditional historiography, which did not make the agency of these black people visible.